The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41467-022-31394-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID certificates on vaccine uptake, health outcomes, and the economy

Abstract: In the COVID-19 pandemic many countries required COVID certificates, proving vaccination, recovery, or a recent negative test, to access public and private venues. We estimate their effect on vaccine uptake for France, Germany, and Italy using counterfactuals constructed via innovation diffusion theory. The announcement of COVID certificates during summer 2021 were associated – although causality cannot be directly inferred – with increased vaccine uptake in France of 13.0 (95% CI 9.7–14.9) percentage points (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 64 publications
2
37
0
Order By: Relevance
“…This announcement led to an unprecedented demand for vaccination. 14 Vaccination rates climbed from about 64% of the population over 20 years old by 11 July 2021 (52% of all ages) to 82% on 5 September 2021 (69% of all ages). Because it targeted pay-for social activities, however, the ‘sanitary pass’ was feared to have a limited impact on vaccination inequities.…”
Section: Introductionmentioning
confidence: 98%
“…This announcement led to an unprecedented demand for vaccination. 14 Vaccination rates climbed from about 64% of the population over 20 years old by 11 July 2021 (52% of all ages) to 82% on 5 September 2021 (69% of all ages). Because it targeted pay-for social activities, however, the ‘sanitary pass’ was feared to have a limited impact on vaccination inequities.…”
Section: Introductionmentioning
confidence: 98%
“…Notification rates are likely to vary over time due to the incidence of infections, testing capacity, and existing policy regulations. Vaccination rates are also likely influenced by the policy framework and the evolution of epidemics and health conditions [ 64 , 65 ]. Individual behavior may change over time or across locations due to the so-called “lockdown fatigue” [ 66 ] or the adaptation to the varying external conditions, including vaccination status and incidence levels.…”
Section: Discussionmentioning
confidence: 99%
“…range. 13,14 In these three countries, however, passports were announced when the fraction of people without a first dose was much larger than Canada (30-35% instead of <20%). In Canada, a study reported slightly higher effects for vaccine passports in Québec (3.1 p.p.)…”
Section: Discussionmentioning
confidence: 99%